Apolipoprotein A5-1131T>C Polymorphism Associated with Lipid Profile in Babol Population - SH Shojaee (Babol University of Medical Sciences, 2010)
BACKGROUND AND OBJECTIVE: Apolipoprotein A5 gene plays an important role in plasma lipid regulation. Protein deficiency of apolipoprotein A5 gene causes an increase in plasma triglyceride. The aim of this study was to assay the effect of apolipoprotein A5-1131T>C polymorphism associated with lipid profile in Babol population.METHODS: This case-control study was performed on 199 people in Babol. They were divided into two groups under supervision of the specialist and with regard to their medical history and files: low triglyceride group (99 persons with triglyceride< 103 mg/dl) and high triglyceride group (100 persons with triglyceride> 150 mg/dl) and their biochemistry and anthropometric parameter were measured. The apolipoprotein A5 gene was amplified by PCR method and polymorphism was revealed by the use of MseI enzyme with RFLP method and then compared.FINDINDS: Allele C frequency in people with high triglyceride was 0.21 and in people with low triglyceride was 0.11 that these differences were statistically significant (p=0.02). Also, significant association was found between serum triglyceride (p=0.016) and C allele in low and high triglyceride groups. Being carrier allele C versus TT genotype increased the chance of high triglyceride OR=1.97 times (95% CI=1.35-3.68).CONCLUSION: Our study confirms the association of the APOA5 -1131T>C polymorphism with triglyceride levels in humans. Therefore, genetically evaluation of subjects with high triglyceride recommends to determine allele and diagnosis of cardiovascular patient.